Evaluation of E-Learning Implementation During The Covid-19 Pandemic: A Case Study At Politeknik Negeri Semarang (POLINES) Indonesia - Hasanudin, Mohamad; Sadida, Afiat; Widyarti, Maria Th Heni; Budiyono, Iwan; Pinandhito, Kenneth; Pradana, Bagas Putra (Indonesian Scientific Publication, 2024)
In early 2020, Indonesia, including the world, faces the massive spread of the Covid-19 virus. The spread of COVID-19 has prompted the President of the Republic of Indonesia through the minister of education to issue Circular Number 4 of 2020 concerning the Implementation of Education Policies in Emergency Times Spread of COVID-19 in a Circular It is explained that the learning process is carried out at home through online learning. This policy means changing the learning method from the majority of face-to-face to online learning. Online learning methods are new to all interested parties: teachers, students, and education management. This phenomenon encourages a study to be carried out that aims to determine the effectiveness of online learning at the Semarang State Polytechnic in achieving curriculum targets. This quantitative research begins with a review of policies and literature related to COVID-19 and online learning, which is continued by using an online questionnaire to collect data obtained from 643 student respondents and 76 lecturers in 5 departments and 18 study programs from 25 study programs in POLINES This study wanted to determine the effectiveness of online using El Nino from 1) Content, 2) Interface, 3) Feedback and assessment, 4) Convenience, 5) Interaction, and 6) Social Influence; research findings from the six variables obtained an overall average index. Which was obtained from the lecturers' respondents was 69%, while the overall average index obtained from student respondents was 73%.